Triggering of Secondary Succession after Forest Fire Breakouts in Shiwaliks, North-West Himalaya - Sharma, Pallvi; Dutt, Harish Chander (Indian Forester, 2017)
As per annotations on surface maps of Kalidhar forest range obtained periodically from an open source Google Earth using 1300 satellites, a gradual decline in the forest cover has been noticed in the last fifteen years. Thinning of forests in accordance with the satellite images reveals that forest fire breakouts in each year during the months of April-August is affecting negativity to the richness or evenness of tree species in the area. However, it is pertinent to reveal that the prescribed functioning of the forest ecosystem after forest fire is lacking in the proposed study area. The post-fire regeneration index of Pinus roxburghii (dominant species) and other plant species has been studied to find out the level of auto-succession in both post-fire regeneration sites and reference site. Patterns of succession deduced from the observations made in sample plots on these sites showed that regeneration in post-fire degraded sites was comparatively higher.